Implementasi Kebijakan Pengelolaan Dana Dekonsentrasi Bidang Kesehatan Pada Dinas Kesehatan Provinsi Banten - Muhammad Revki Iboyma; Agus Sjafari; Juliannes Cadith (Universitas Serang Raya, 2023)
The health deconcentration fund is one of the funding schemes for the regions in the context of delegating functions that fall under the authority of the central government to regional governments in certain areas to support the achievement of national development. This study aims to analyze the implementation of deconcentration fund management policies in the health sector at the Banten Provincial Health Office and explain the inhibiting factors for the implementation of deconcentration fund management policies in the health sector at the Banten Provincial Health Office. This study uses a qualitative method using the policy implementation model of Edward III which states four variables, namely communication, resources, disposition and bureaucratic structure. Data collection was carried out through interviews with 7 informants and a study of documentation of reports on the management of deconcentration funds at the Banten Provincial Health Office for the 2019-2022 period. The results of the study concluded that the implementation of deconcentration fund management policies in the health sector at the Health Office of Banten Province was still not effective. This is caused by the communication aspect which has not been maximized and the inadequate qualification of adequate resources for the management of deconcentration funds. Factors inhibiting the implementation of deconcentration fund management policies in the health sector include the low allocation of funds from the state budget which is not sufficient, the principles of efficiency and effectiveness that are not yet clear, the absence of good coordination in terms of dissemination of implementing regulations, and the lack of optimal guidance and supervision of deconcentration effective.